Radiological malformations of the ear in Pendred syndrome. - Phelps, P; Coffey, R; Trembath, R; Luxon, L; Grossman, AB; Britton, K; Kendall-Taylor, P; Graham, J; Cadge, B; Stephens, S; Pembrey, M; Reardon, W (1998)
Pendred syndrome comprises the association of severe congenital sensorineural deafness with thyroid pathology. Although it is the commonest form of syndromic hearing loss, the primary genetic defect remains unknown. The variable clinical presentation allied to the difficulty in securing the diagnosis have resulted in relatively poor documentation of the radiological features of this syndrome. We now present data on 40 patients, all complying with strict diagnostic criteria for the disorder, and describe our experience of the prevalence of specific malformations of the inner ear as well as comparing the relative merits of computed tomography (CT) and magnetic resonance imaging (MRI) in the investigation of this inherited condition. Deficiency of the interscalar septum in the distal coils of the cochlea (Mondini deformity) was found to be a common but probably not a constant feature of Pendred syndrome. However, enlargement of the endolymphatic sac and duct in association with a large vestibular aqueduct was present in all 20 patients examined by MRI. We conclude that thin section high resolution MRI on a T2 protocol in the axial and sagittal planes is the imaging investigation of choice.